2019
DOI: 10.1002/cjce.23471
|View full text |Cite
|
Sign up to set email alerts
|

Activated carbon impregnation with ag and cu composed nanoparticles for escherichia coli contaminated water treatment

Abstract: This study aimed to produce modified granular activated carbon (GAC) by low concentrations of silver (Ag) and/or copper (Cu) nanoparticles with antibacterial capacity for application in water purification. Modified porous materials were produced from the vacuum impregnation method, at the concentrations (mass of metal/mass of activated carbon) of Ag 8 x 10−4 g/g (Ag 0.08 %), Cu 1 x 10−2 g/g (Cu 1 %), and Ag 8 x 10−4 g/g + Cu 1 x 10−2 g/g (Ag 0.08 % Cu 1 %). The reduction of the metal salts in NPs of Ag and Cu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 80 publications
0
3
0
3
Order By: Relevance
“…In the corresponding EDX spectrum, Table 1, the elemental composition of GAC can be observed with the presence of carbon, oxygen, and some elements such as aluminum, silica and chlorine, were also identified in studies reported by other authors (Giri et al, 2012;Haro et al, 2012;Mohan et al, 2011;Qu et al, 2009). In the EDX spectra of GAC/Mn/Fe, the presence of Mn and Fe was also observed, in addition to signs referring to the elements commonly present in GAC samples of vegetable origin (Arakawa et al, 2019b).…”
Section: Adsorbent Characterizationmentioning
confidence: 84%
“…In the corresponding EDX spectrum, Table 1, the elemental composition of GAC can be observed with the presence of carbon, oxygen, and some elements such as aluminum, silica and chlorine, were also identified in studies reported by other authors (Giri et al, 2012;Haro et al, 2012;Mohan et al, 2011;Qu et al, 2009). In the EDX spectra of GAC/Mn/Fe, the presence of Mn and Fe was also observed, in addition to signs referring to the elements commonly present in GAC samples of vegetable origin (Arakawa et al, 2019b).…”
Section: Adsorbent Characterizationmentioning
confidence: 84%
“…Figure 1 presents a schematic illustration of localized MIC on aluminum alloy, according to the concepts described in [14]. [14] The beneficial properties of silver and its ions are not limited only to their confirmed bactericide properties, recently widely investigated [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Materials, containing this element possess also definitively catalytic [41][42][43] and photocatalytic [44][45][46][47][48][49][50][51][52][53][54][55][56][57] properties.…”
Section: Introductionmentioning
confidence: 99%
“…Dentre os adsorventes mais utilizados no mercado hoje, podemos citar as argilas, o carvão ativado, óxido de grafeno e algumas partes de plantas ou outros materiais com alto teor de carbono, como resíduos de frutas e biomassas. E de acordo com Arakawa et al (2019), nanopartículas compostas por elementos como prata (Ag), zinco (Zn), níquel (Ni), ferro (Fe) e platina (Pt) têm atividade antibacteriana e pode ser usado em diversas áreas, como o campo médico, processamento de alimentos, catálise e tratamento de água.…”
Section: Adsorventes No Tratamento De áGuaunclassified